Pengembangan Aplikasi To-Do List Adaptif Berbasis Android untuk Intervensi Distraksi Digital - Michael Reynald Manoppo Manoppo; Salvius Paulus Lengkong Lengkong; Salaki Reynaldi Joshua Salaki (Riau Jurnal Teknik Informatika, 2026)
Academic procrastination is a common problem among university students and can be intensified by digital distractions from social media notifications and entertainment applications on smartphones. A preliminary study involving 40 students from the Faculty of Engineering at Sam Ratulangi University showed that 72.5% of respondents frequently completed assignments close to deadlines, 80.0% were often distracted while working on assignments, and 60.0% experienced difficulty maintaining focus. Existing to-do list applications are generally passive, as they mainly function as task recording and reminder tools without active mechanisms to help users limit digital distractions. This study aims to design and develop an Android-based adaptive to-do list application named MyTask, equipped with proactive intervention features. The development method used was Research and Development (R&D) with the ADDIE model. The application was developed using a hybrid approach, combining a Flutter-based user interface with native Android services to support distraction application blocking and notification filtering based on the urgency level of user tasks. User experience evaluation was conducted with 20 student participants using the User Experience Questionnaire (UEQ), which consists of 26 items across six measurement scales. The results showed that all UEQ scales achieved an Excellent classification, with the highest score obtained by Efficiency (2.450) and the lowest score by Novelty (1.950). These findings indicate that MyTask is feasible to use and well received from a user experience perspective. However, this study did not directly measure the application’s effectiveness in reducing procrastination; therefore, further experimental evaluation is required.